(untitled) (Bangladesh Journal of Psychiatry, 2022)
Adolescence is a crucial period for developing social and emotional habits important for mental well-being. Despite their relevance as a leading cause of disability in this age group, the mental health needs of adolescents are neglected. The aim of this study was to find out the proportion of adolescent mental health problems. It was a cross-sectional study which was conducted from October 2019 to September 2020 in Khwaja Yunus Ali Medical College, Sirajganj. Total 129 adolescents of both sexes aged between 13 to 19 years were evaluated through face to face interview using a semi structured questionnaire and Depression Anxiety Stress Scale 21 (DASS 21). The results showed that, 55.8% were male and 44.2% were female. It was found that, 42.6%, 55.8% and 44.2% had depression, anxiety and stress respectively. It was also found statistically significant of parent child relationship in mental health problems (P<0.05). This study indicated that, mental health was a potential factor that could have an impact on the mental health status of adolescents. Further multi-centered prospective and population-based studies should be designed to find out the exact situation. Bang J Psychiatry 2022;36(1):1-5